A semi-automated method for the integrated evaluation of half-life and metabolic soft spots of discovery compounds. (July 2012) - Grubb, Mary F; Humphreys, William G; Josephs, Jonathan L
Background: An integrated method that provides rates of both parent disappearance and metabolite formation was developed.Results: Buspirone, mirtazapine and verapamil were used as model compounds in developing the method. Incubations were carried out on a robotic platform. Qualitative analysis of metabolites in 30 µM samples was conducted by data-dependent HPLC–MS/MS on a high-resolution instrument. Quantitative analysis of the parent compound and metabolites in 0.5 µM samples was conducted by full-scan MS 2 with product ion extraction using an ion trap mass spectrometer. Data generated for the compounds included half-life and intrinsic clearance of the parent molecule, characterization of metabolites and relative rates of metabolite formation. A correction factor was used to convert MS responses of metabolites in 0.5 µM samples to UV areas in order to compare relative metabolite concentrations.Conclusion: The approach allows for the investigation of a set of six compounds simultaneously, with a turnaround time of 1 week or less.